2017
DOI: 10.1155/2017/6878263
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Complications of Pregestational and Gestational Diabetes in Saudi Women: Analysis from Riyadh Mother and Baby Cohort Study (RAHMA)

Abstract: The objectives of this study were to estimate the burden of diabetes and to explore the adverse pregnancy outcomes associated with pregestational diabetes mellitus (pre-GDM) and gestational diabetes mellitus (GDM) among the Saudi pregnant population. In this subcohort, we compared the maternal and the neonatal outcomes of diabetic women with pre-GDM and GDM to the outcomes of nondiabetic mothers who delivered during the same period. From the total cohort, 9723 women participated in this study. Of the participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
84
7
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(109 citation statements)
references
References 32 publications
14
84
7
4
Order By: Relevance
“…These cohorts consistently found that pregnant women with pre-GDM or GDM were at increased risk of various adverse maternal and birth outcomes including CS delivery, macrosomia, and preterm delivery [26,48,67,88]. Pre-GDM was also independently associated with CS delivery (adjusted odds ratio "aOR," 1.65), induction of labor (aOR, 1.67), macrosomia (aOR, 1.40), stillbirth (aOR, 3.66), and APGAR score < 7 at 5 min (aOR, 3.82) [67]. Various unfavorable health outcomes were more common in grand multipara compared to primigravida mothers [82,114] (see Additional file 3: Table S2).…”
Section: Maternal or Reproductive Exposuresmentioning
confidence: 87%
See 3 more Smart Citations
“…These cohorts consistently found that pregnant women with pre-GDM or GDM were at increased risk of various adverse maternal and birth outcomes including CS delivery, macrosomia, and preterm delivery [26,48,67,88]. Pre-GDM was also independently associated with CS delivery (adjusted odds ratio "aOR," 1.65), induction of labor (aOR, 1.67), macrosomia (aOR, 1.40), stillbirth (aOR, 3.66), and APGAR score < 7 at 5 min (aOR, 3.82) [67]. Various unfavorable health outcomes were more common in grand multipara compared to primigravida mothers [82,114] (see Additional file 3: Table S2).…”
Section: Maternal or Reproductive Exposuresmentioning
confidence: 87%
“…Thirty-four cohort studies (42.0%) were identified as a prospective design (19 in [81], and three in the UAE). Fiftytwo (64.2%) cohort studies enrolled pregnant mothers at varying stages of their pregnancy with different characteristics such as diabetic and non-diabetic mothers [26,67], obesity [42,47,54], singleton [41,48,99] or triplet pregnancies [91], teenage women [112], multipara women [82,86,98], and women with systemic lupus erythematosus (SLE) [27]. Eight studies (9.9%) enrolled pregnant mothers at varying stages after delivery [24,49,58,59,81,84,88,99].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Saudi Arabia, the rising trends of obesity have led to greater incidence of T2DM, with greater proportions of pregnant women with undiagnosed T2DM [3]. A cohort study from Riyadh, Saudi Arabia, estimated the prevalence of Pre-GDM and GDM to be around 4.3% and 24.2%, respectively, indicating a great burden of diabetes among pregnant women in Saudi Arabia [4]. Pregnancy is a period of specific nutritional needs to support health of the mother and the fetus [5].…”
Section: Diabetology and Metabolic Syndromementioning
confidence: 99%